Dietary Practices Among Pregnant Women in Rural Amhara, Ethiopia. (7th June 2021) - Workneh, Firehiwot; Eglovitch, Michelle; Shiferaw, Tigest; Shiferie, Fisseha; Amanuel, Hanna; Tadesse, Amare Worku; Worku, Alemayehu; Isanaka, Sheila; Lee, Anne CC; Berhane, Yemane
Abstract: Objectives: Malnutrition affects 25% of women in Ethiopia. We are conducting a study to determine the impact of a prenatal nutrition intervention on maternal and infant health in Ethiopia. The objective of this formative study was to better describe dietary practices among pregnant women and community members in rural Ethiopia prior to initiation the parent study. Methods: This formative study was conducted from October-November 2018 among pregnant women and community members in the rural Amhara region of Ethiopia, prior to the "Enhancing Nutrition and Antenatal Infection Treatment (ENAT)" study [ISRCTN15116516]. 28 in-depth interviews (IDIs) were conducted among 16 pregnant women and 12 community members. IDIs were recorded, transcribed, and translated. We used a grounded theory approach and inductive reasoning for content analysis of interview transcripts. Results: Fasting norms in the Ethiopian Orthodox religion had a significant impact on dietary behaviors which occurs for more than 200 days annually. Community members indicated that fasting during pregnancy is common and is also supported and encouraged by religious leaders and community members. Accordingly, women adhered to fasting restrictions during pregnancy, and many women maintained a vegan diet under direction of local religious leaders. Furthermore, many women reported restricting dietary intake in pregnancy to prevent growth of the fetus because of the concern for obstructed labor. A women's diet depended on her husbands'/family earnings and household food preferences. Sharing of meals is a cultural norm; the husband is served first, with the remaining portions to the pregnant women/children. Pregnant women in the area also reported regular consumption of a locally brewed alcohol ("tella"), as it is believed to have lower alcohol levels. These findings demonstrate the impact of traditional and cultural beliefs on dietary decisions amongst pregnant women in this population. Conclusions: Reduced food intake in pregnancy is common in this population, due to fasting, reduced appetite, and food restriction to avoid pregnancy complications. Context-specific interventions are needed, and this formative work will inform the future delivery and education regarding nutrition interventions in rural Ethiopia. Funding Sources: Bill & Melinda Gates Foundation (OPP1184363).